Analysis of Student Satisfaction Level of Library Services - Magfirah, Nurul; Saleh, Muhammad; Zulfah, Zulfah (Institut Agama Islam Negeri Parepare, 2022)
This study aims to describe the level of student satisfaction with the services of the IAIN Parepare Library. Data collection was carried out using a questionnaire (questionnaire) with a survey method. The population in this study were 5,960 students and 100 students were taken as a sample using simple random sampling technique. The analysis used is quantitative descriptive analysis. The results showed that the index of student satisfaction with the services of the Library of the State Islamic Institute (IAIN) Parepare was at 73.34% which was included in the satisfied category. Of the 20 indicators considered, they are translated into 5 sub-variables, namely: 1. Tangibles (direct evidence), 2. Reliability (reliability), 3. Responsiveness, 4. Assurance, 5. Empathy. Of the five variables that become student satisfaction in services at the Parepare State Islamic Institute (IAIN) Library, the main consideration for the direct evidence dimension is in the satisfied category with a percentage of 74%. For the reliability dimension with a percentage of 74.3% or in the satisfied category. The power dimension of the ladder is in the satisfied category with a percentage of 73.6%. The guarantee dimension with a percentage of 71.85% or is in the satisfied category and for the empathy dimension is in the satisfied category with a percentage of 72.95%.